Processing of municipal solid waste resources for a circular economy in China: An overview. (1st June 2022) - Awasthi, Sanjeev Kumar; Sarsaiya, Surendra; Kumar, Vinay; Chaturvedi, Preeti; Sindhu, Raveendran; Binod, Parameswaran; Zhang, Zengqiang; Pandey, Ashok; Awasthi, Mukesh Kumar
Graphical abstract: Highlights: Discussed waste-to-energy methods for the treatment of municipal solid waste (MSW). Examined the energy recovery possibilities of China's municipal solid waste. A comparison between Chinese provinces and chosen developed regions is made. Evaluated conventional and unconventional solutions for reclaiming energy from MSW. Abstract: To realize the management of municipal solid waste (MSW), China uses MSW conversion technology to generate fuel and other byproducts through which the operating costs (e.g., capital and operational) are maintained to some extent. The amount of MSW produced per capita in China is a serious problem. Therefore, a circular economy method was investigated that can not only manage MSW safely but also convert MSW into energy to meet the growing energy demand. This study summarized the current status of MSW treatment and gives an overview of several waste-to-energy conversion technologies by describing their possible and existing situation in China and identifying related challenges. Currently, none of the single technologies can effectively realize waste-to-energy conversion. Only in this way can waste-to-energy technology achieve commercial success and community preparedness.